Implementation of the book tuhfatul athfal in maintaining the quality of qur'an recitation among students of Pondok Pesantren Tahfidzul Qur'an Bilal Bin Rabah Sukoharjo, Central Java - Muhammad Wijdan Aly Al Adni; Indah Nurhidayati; Izzun Khoirunnisa; Abdu Robbi Rasul Nuh Al Hawary (At Turots: Jurnal Pendidikan Islam, 2024)
The implementation of the Tuhfatul Athfal book in Tajweed education at Pondok Pesantren Tahfidzul Qur'an Bilal bin Rabah Sukoharjo is the focus of this study, given the importance of maintaining the quality of Quranic recitation. This study aims to analyze the implementation of this book, identify the factors affecting its success, and develop strategies to address gaps in Tajweed understanding and application among students. The research employs a qualitative descriptive method, with data collected through in-depth interviews, participatory observations, and documentation. The findings indicate that the Tuhfatul Athfal book is effectively implemented through interactive and practice-based teaching methods. However, challenges such as differences in students' levels of understanding, limited time for guidance, and students' motivation were identified. To address these gaps, it is recommended to adjust teaching methods, provide additional guidance time, use technology as a supplementary tool, and strengthen motivation and support from instructors. By applying these strategies, it is hoped that the quality of Quranic recitation among students will improve and the gaps in Tajweed understanding will be minimized.